A Magyar Képzőművészeti Egyetem Könyvtárának és Művészeti Gyűjteményének története - Blaskóné Majkó, Katalin; Bojtos, Anikó (Per Aspera ad Astra, 2016)
The National Hungarian Fine Arts Association was established in 1861 and aimed to set up an art academy in Hungary in order to ensure the independent improvement of national art. One of the members – Gusztav Keleti – was entrusted with visiting all of the most important art academies in Europe and investigating their teaching methods. Based on his observations, the Hungarian Royal School of Model Drawing and Draughtsmanship Teacher Training, predecessor of what is the Hungarian University of Fine Arts today, was established on May 1871 in a rented flat, under 6 Rombach (today Rumbach Sebestyén) Street. Gusztáv Keleti got appointed as the director, who formed the collection of the library with the help of the teachers from the very beginning. Apart from books, model drawings (mostly lithographs, photomechanical prints, later photographs) and plaster copies of famous sculptures were acquired as well. The institution moved into its permanent home (Andrássy Street 71.) in 1876, and the library got a spacious hall on the first floor. The new building was planned by one of the teachers, Lajos Rauscher. In 1895 the collection found its current premise in the other part of the university building facing Izabella Street. The first director of the library was János Greguss (1878–1888), followed by Szilárd Várdai (1888–1923), Antal Horn (1923–1947), László Cs. Szabó (1947–1949) and János Faludi (1950–1956). The institutional reform, carried out by Károly Lyka from 1920, abolished the model drawing courses, so a huge part of the library collection lost its importance. The rediscovery of the treasures, hidden in the old furniture, happened only after 1989. The Art Collection of the Hungarian University of Fine Arts consists of more than 10.000 priceless drawings and prints, including Japanese woodcuts and an Art Nouveau placard collection. Apart from that more than 12.000 unique photographs, made by famous Hungarian and European artists, and a stunning set of optical instruments are preserved. Due to the works of our existing students, contemporary art is also represented in the collection. Fotó: Fortepan / Budapest Főváros Levéltára / Klösz György fényképei